JOINT POLICE COOPERATION COMMITTEE POLRI-PDRM SEBAGAI UPAYA INDONESIA DAN MALAYSIA DALAM MENJAGA KEAMANAN PERBATASAN PERIODE 2015-2017 - Adrian Pramana Putra; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research study of diplomacy and strategy analyses about the Indonesian and Malaysian efforts to protect border between two countries. The Purpose of this research explain about Indonesia-Malaysia defence and security cooperation general condition, especially in border region against transnational organized crime. As the strategy of the two countries to cooperate throgh Joint Police Cooperation Committee between Polri and PDRM. This research focused on the effort of the cooperation to fight transnational crime in border region.Indonesia-Malaysia border lies within seas and land. Start with in Malacca Strait, South China Sea, and in Borneo Island. Occurance of globalization made it people easier to cross between border legally nor illegally. This event used by crime actor to widen their crime such as drug smuggling, human trafficking, piracy and illegal fishing. To overcome this problem Indonesia and Malaysia had to commit a strategy and it is through burden sharing cooperation to put aside their political conflict and focus on bigger threat to their people and sovereignity.This research used qualitative methods which is done by explanning the case based on facts. The collecting data techniques used in this research in studying the case is library research in the form of journals, books, official documents report, and website. Writer also used observation by attending one of the cooperation meeting as observer. The theory that apllied in this research is strategy theory under the realism perspective in nation-state analysis. Within the human security concept which is saw threat of a country is not from another country anymore.Key Words: Effort, Border security, Joint Police Cooperation Committee Polri-PDRM, Transnational organized crime